Post-marketing safety concerns with trofinetide: a disproportionality analysis of the first therapeutic agent for Rett syndrome based on the FDA adverse event reporting system (FAERS) - Yu, Xihui; Zhong, Jiahong; Lin, Zhuomiao; Fu, Hongbo; Zhang, Yaofeng (Frontiers in Pharmacology, 2026)
ObjectiveRett syndrome (RTT) is a severe, rare and chronic disease that necessitates long-term treatment. In March 2023, trofinetide was approved by the US Food and Drug Administration as the first treatment for RTT. Because of the constraints of clinical trials, certain delayed and infrequent adverse events (AEs) may go unreported, especially in orphan disease. Further research is required to investigate the potential AE signals of trofinetide in real-world scenarios, identify rare and severe AEs associated with this treatment, and promote the safe use of trofinetide among RTT patients.MethodsThe data were extracted from the FAERS database from the first quarter of 2023 to the fourth quarter of 2024. Signal mining was conducted using frequency and Bayesian methods to identify positive signals associated with trofinetide. In order to obtain similar reports, the generic name “trofinetide” and commercial name “DAYBUE” were utilized.ResultsA total of 3,293,302 AE reports were collected, with 15,266 AE reports from 2,824 patients related to trofinetide designated as the primary suspected drug. All the reports were from the United States. Signal mining identified 25 system organ classes (SOCs), involving 155 preferred terms (PTs). Gastrointestinal disorders had the highest report count, with diarrhoea being the most prominent AE with high report numbers and signal strength. Several noteworthy AEs except for gastrointestinal disorders were identified which are not included on the drug label, such as nasopharyngitis, decreased appetite, weight decreased, gastroenteritis viral, influenza and irritability. Time-to-onset analysis shows that most AEs occurred in 0–30 days.ConclusionThis study unveils certain potential risks associated with trofinetide in real-world applications. Medical staffs should pay more attention to AEs of patients on the first month.